AUTHORITY TO DEVELOP INTERNATIONAL TOURISM UNDER ECONOMIC REFORMS - Ravshanjon Ismoilov; Matlubakhon Abdimanabovna Kuymuratova (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In the article drew attention to the peculiarities of the development and regulation of the tourism industry based on the study of organizational and economic aspects of its functioning in a modern economy, and examined the factors that contribute to the effective use of the potential of tourism development. The development of the international tourism market is directly related to the issues of restoration of caravan routes. Uzbekistan has been and still is at the center of these ancient roads, and its participation in the activities to restore them is very necessary. This process is related to the level of development of the road system. Considering this, great attention is paid to the construction of road networks in the republic.